Rancang Bangun Mesin Sangrai Sampel Biji Kopi Elektrik Kapasitas 250 Gram - Rahman Azis Prasojo; Heri Sungkowo; Dinda Ayu Amalia; Rahmad Dwi Pramudya; Muhammad Fahmi Hakim; Bakti Indra Kurniawan; Sukamdi (Elposys: Jurnal Sistem Kelistrikan, 2023)
Coffee is one of the beverages with a distinct flavor profile. Coffee production continues to grow in response to community demands. A wide variety of coffee flavors have been developed, necessitating an effective coffee processing method, such as roasting. While many coffee production processes employ roasting machines with high capacities, smaller industries may incur losses when using such machines due to their production needs, which involve creating new coffee flavor samples. To address these challenges, a solution is proposed: the creation of a drum-based coffee bean sample roasting machine that utilizes the convection method. The machine manufacturing process involves calculating the drum capacity, heater specifications, motor rotation, and air flow. A 2000 Watt heater is chosen, accompanied by a maximum drum capacity of 250 grams. The driving motor is a 12 V DC motor. The combined power of the motor components totals 1520 Watts, and the overall heating capacity can achieve temperatures of up to 300ºC. Performance testing of the roasting machine is conducted under conditions where all components are functioning correctly. The final roasting results exhibit even distribution, with a preheating temperature range of 190-200ºC for approximately 15 minutes roasting time.